ANALYSIS OF STANDARD ANIMAL PROTEIN PORTIONS AND INGREDIENT COSTS WITH THE SELLING PRICE OF ANIMAL DISHES AT KARAWANG CATERING - Ramadhani, Nayla; Andriani, Eka; Elvandari, Milliyantri (HEARTY, 2025)
Portion standards and ingredient costs are two important interrelated components in determining the selling price of a dish. This study aims to analyze the relationship between animal protein portion standards and ingredient costs on the selling price of animal-based dishes at Catering K in the Karawang region. This is a quantitative study with a cross-sectional design conducted from May to June 2025. The study population includes all data on portion standards for animal-based side dishes (chicken, eggs, meat, fish, squid, shrimp), ingredient costs, and the selling price of animal-based dishes. Data collection techniques used total sampling with a total of 28 dishes. The results of the study show that portion standards are divided into three sizes, namely I (35–80 g), II (42–100 g), and III (49–120 g), with an average compliance rate of 99.1%. Ingredient costs and selling prices were also divided into three categories according to portion size. The Spearman test results showed a significant relationship between portion standards and the selling price of animal-based dishes, with a p-value of 0.020 (p<0.05). The larger the portion size standard set, the higher the selling price charged. The Spearman test results also showed a significant correlation between ingredient costs and selling prices, with a p-value of 0.000 (p<0.05). The higher the ingredient costs incurred, the higher the selling price set.